Factors influencing awareness of beverage grading policies and their association with beverage consumption patterns - Jiaxing Li; Jingyi Zhang; Xiaowen Hu; Yu Sun; Jingyao Yu; Peiying Wang; Junhui Tang; Meihui Hua; Kefan Chen; Lixin Na (Journal of Health, Population and Nutrition)
Abstract Background Given the current lack of government-led front-of-package nutrition labeling policies in China, research on Chinese consumers’ genuine perceptions of nutrition labels and their association with healthy behaviors remains scarce. Notably, Shanghai’s beverage grading policy stands out as one of the rare existing initiatives, providing a valuable opportunity to explore public awareness of the policy, its potential determinants, and its associations with consumer choices. Design To gain a clearer understanding of public perceptions of the beverage grading policy, a survey was conducted across seven hospitals in Shanghai, yielding 931 valid responses for analysis. Analysis We conducted descriptive analyses and multinomial logistic regression to explore factors associated with public awareness of the policy. We also examined how different levels of awareness were related to beverage consumption patterns. Results More than half of the respondents were unaware of the policy. Greater awareness was associated with being female, younger, more highly educated, having a lower BMI, and paying closer attention to food nutrition and ingredient labels. However, respondents with nutrition-related chronic diseases and dietary restrictions did not exhibit significantly higher awareness. Individuals more familiar with the policy tended to purchase non-water beverages more frequently and, following its widespread implementation, adopted a more practical approach to their beverage choices. Moreover, higher policy awareness correlated with increased attention to sweeteners and trans fats. Conclusions Overall, this study found that public awareness of the beverage grading policy remains low, highlighting persistent research gaps in health-promotion efforts—particularly regarding the psychological mechanisms linking policy awareness to consumption behavior, and the media’s role in shaping consumers’ understanding of key nutrients. Looking ahead, the broader implementation of front-of-package labeling in China will require addressing entrenched systemic challenges.